Diseño e implementación de un sistema inteligente para caracterización del hormigón con tecnología radar - Erika Tatiana, Mayorga Mayorga. (2019)
Now days, the study of the durability of concrete is a subject of great importance, since a large number of structures built during the twentieth century have shown sings of premature deterioration, the techniques for obtaining the compressive strength of concrete most used represent high costs and relatively large machines, limiting their mobility, which is why this study deals with the non-destructive technique of electromagnetic waves. The technique is based on the propagation of electromagnetic impulses, an antenna located on the surface of the concrete transmits a wave that propagates, towards its interior, being reflected in the interfaces where there is a dielectric contrast. The response of the material, made up of all the waves reflected in the interval of maximum pairs of electromagnetic waves. The training of the nearest neighbor KNN algorithm, presented a reliability of 92.3%, having the ability to estimate values of the probability posteriori that a test tube belongs to the range of resistances. Finally, the validation was carried out with the help of a testing machine, where the resistance of the concrete specimens was compared with the predictions obtained through the developed system, in 4 out of 5 specimens had a favorable result. Demonstrating in this way, the possibility of assessing the resistance of concrete by combining radar technology and the use of automatic learning algorithms.